Hidup Kristen yang utuh berdasarkan Filipi 4:9 - Eveline, Sjanette; Pasaribu, Nadia; Juanda, Juanda (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2024)
In contemporary times, Christian living has lost its essence. This is evident in how Christian life today has strayed far from God’s plan as outlined in the Bible. Many Christians engage in religious practices purely as acts of ritualistic obedience. Studying and understanding Scripture is often reduced to the pursuit of knowledge alone. Acts of goodness are performed with manipulative intentions, aiming to reap manifold returns from their actions. Christians have increasingly abandoned the essential values that should define their faith. In this paper, the author employs the methods of literature study and textual analysis. Based on findings from various sources, the author concludes that a holistic Christian life must be built upon a deep understanding of God’s Word. The Word of God is not given to satisfy human curiosity about God or merely to recount what He has done in the past or will do in the future. Studying, hearing, and receiving God’s Word must culminate in putting that Word into practice.